2013
DOI: 10.9775/kvfd.2012.7044
|View full text |Cite
|
Sign up to set email alerts
|

Increased Glucose Uptake and Insulin Binding Activity of Nerium Oleander in Hepatocytes and Adipocytes

Abstract: Type 2 diabetes mellitus (DM) affects a large population worldwide. DM is often considered as a syndrome of disordered glucose metabolism. Current conventional drug therapies for DM are usually insufficient and medicinal herbs with antihyperglycemic activities are increasingly sought by diabetic patients and health care professionals. Nerium Oleander (N.O.) is known to be effective in lowering of postprandial blood glucose in DM patients as a folk remedy. In this study we aimed to evaluate effect of N.O. disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Hydrodistillation (an original method) was used to obtain leaf distillate from N. oleander in this study. The distillate was not toxic to mammary carcinoma MCF-7 cells according to the results which are very similar to the findings for liver cells HEP3B by Yazihan et al [11] . We found also that the distillate has antagonistic interaction with paclitaxel and vincristine which also show that it does not have toxic effect on cell proliferation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Hydrodistillation (an original method) was used to obtain leaf distillate from N. oleander in this study. The distillate was not toxic to mammary carcinoma MCF-7 cells according to the results which are very similar to the findings for liver cells HEP3B by Yazihan et al [11] . We found also that the distillate has antagonistic interaction with paclitaxel and vincristine which also show that it does not have toxic effect on cell proliferation.…”
Section: Discussionsupporting
confidence: 89%
“…We found also that the distillate has antagonistic interaction with paclitaxel and vincristine which also show that it does not have toxic effect on cell proliferation. According to the previous studies, N. oleander distillate is not toxic to animal models, so N. oleander may be used in treatment of some diseases [11] . The effects of N. oleander distillate as food supplement on rats taking high fat diet were investigated also by the same group.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Regulation of lipid metabolism which is controlled by very complex metabolic pathways and by diet type is enlightened to some extent at the gene expression level. It is also revealed that non-toxic N. oleander leaf distillate (Kars et al, 2013;Yazihan et al, 2013) may be used as a supplement to regulate cholesterol metabolism in animal models. Further functional and pharmacological assessments will be conducted by our group to suggest the unique N. oleander leaf distillate as a medicinal food supplement.…”
Section: Discussionmentioning
confidence: 99%
“…Some types of N. oleander leaf extracts prepared in different solvents were found to be anti-proliferative in cancer cells (Fu et al, 2005). Nerium oleander leaf distillate, however, was declared by our group as non-toxic to normal and cancer cells (Kars et al, 2013;Yazihan et al, 2013).…”
Section: Introductionmentioning
confidence: 90%